Wooden bracket at Jagannath Mahadev Temple - Ghosh, Ayan (2023)
The Jagannath Mahadev Temple has anthropomorphic wood-carved brackets supporting the roof. These are in the form of female musicians playing a variety of musical instruments. They are heavily decked in jewelry and wear a blouse and skirt-like garment. The brackets are painted in bright colors and add an element of playfulness to the overall decor of the temple.